Identification of strategic groups using relationship marketing criteria: A cluster analytic approach in professional services - Panayides, Photis (My University, 2002)
The integration of marketing and strategy advocated by contemporary marketing thought permeates the underlying objectives of this article. These objectives include the identification of strategic groups on the basis of marketing relationships in a professional service context and the making of inferences with respect to achieving a competitive advantage as expounded by the resource-based view. The article reviews the concepts under scrutiny prior to applying qualitative and quantitative techniques to identify the existence of four strategic groups in the context of professional ship management firms. Practice and research implications for marketing and competitive advantage of professional service firms are thereby discussed.
Keywords: Service industries; Relationship marketing; Competitiveness (Economics); Shipping--Management